Does Forecast Combination Improve Norges Bank Inflation Forecasts? - Hilde C. Bjørnland; Karsten R. Gerdrup; Anne Sofie Jore; Christie Smith; Leif Anders Thorsrud (Norges Bank, 2009)
We develop a system that provides model-based forecasts for inflation in Norway. Forecasts are recursively evaluated from 1999 to 2008. The performance of the models over this period is then used to derive weights that are used to combine the forecasts. Our results indicate that model combination improves upon the point forecasts from individual models. Furthermore, when comparing the whole forecasting period; model combination outperforms Norges Banks own point forecast for inflation at the forecast horizon up to a year. By using a suite of models we allow for a greater range of modelling techniques and data to be used in the forecasting process.
hdl:11250/2497644
Keywords: E52; E37; E47; 330; forecasting; forecast combination